THE EFFECT OF SOCIALIZATION REGARDING THE IMPORTANCE OF GIVING VITAMIN A TO THE PREVENTION OF CHILDREN WITH SPECIAL NEEDS FOR BLINDNESS - Nenden Siti Rohmah; Asep Bayu Dani Nandiyanto (JURNAL RISET RUMPUN ILMU KEDOKTERAN, 2022)
The Intra Uterin Device (IUD) Family Planning (FP) Program in Indonesia has been declared less successful, in its implementation until now it has experienced obstacles that are felt, among others, there are still many PUS who are not interested in using IUD. Data from the Batam City Health Office in 2018 obtained the use of IUD as much as 3.8%, Implant 5.6% FOM 0.6% and MOM 0.3%. From these data, it was obtained that the use of IUD birth control was still very low compared to Implant.The purpose of this study was to determine the relationship between husband support and maternal interest in the selection of IUD contraceptives in the work area of the Bulang Health Center, Batam City.This study used an analytical design with a cross-sectional design. The sample selection was carried out by purposive sampling of 64 respondents. The independent variable in this study was husband support, while the dependent variable was the mother's interest in the selection of IUD contraceptives. Data collection of independent and dependent variables using questionnaire measuring instruments. Data processing includes editing, coding, scoring, tabulating. The analysis used is a univariate analysis using a frequency table to describe each variable and bivariate analysis using the Chi-Squere test.The results of the analysis using the Chi Square Test obtained probability values (p value) = 0.001 (p value >0.05).